2013
DOI: 10.1111/itor.12002
|View full text |Cite
|
Sign up to set email alerts
|

Impact analysis of logistics facility relocation using the analytic hierarchy process (AHP)

Abstract: Facility relocation has a long-term impact on business competitiveness in terms of cost efficiency, service level, and accessibility to marketplace. This paper investigates the impacts of relocating a company's logistics facility. Specifically, a case study of a logistics service provider for a bank, whose services include cash pick-up and deliveries, and ATM refill, is conducted. Some of the major logistics issues caused by the relocation of the company's distribution center are identified through process obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The topics identified have undergone supply chain and distribution network, warehouse location and customer service with the AHP application combined with Mixed Integer Linear Programming [41]; Genetic Algorithm [45], [46] and [49]; Goal Programming [51], as can be observed in Table 5. A drill down of the citation network was performed, having identified some publications as successors with the following topics: supplier selection, distribution center network, supply chain integration and collaborative planning, forecasting and replenishment [52], [53], [54] and [55].…”
Section: Discussionmentioning
confidence: 99%
“…The topics identified have undergone supply chain and distribution network, warehouse location and customer service with the AHP application combined with Mixed Integer Linear Programming [41]; Genetic Algorithm [45], [46] and [49]; Goal Programming [51], as can be observed in Table 5. A drill down of the citation network was performed, having identified some publications as successors with the following topics: supplier selection, distribution center network, supply chain integration and collaborative planning, forecasting and replenishment [52], [53], [54] and [55].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, concluded that because of the availability of data, the impact of infrastructure on regional development has become the basic criterion [6]. In 2013, other researchers argued that the effect of infrastructure on economic development varies between industrial groups and modes of transport [7].…”
Section: The Infrastructurementioning
confidence: 99%
“…Among the MCDM approaches, the most used one is AHP because of its advantages over others (Wang, Chang 2007;Opasanon, Lertsanti 2013). As Saaty (1980) indicates, the most noted advantages of the AHP approach are; its ability to handle the inconsistencies in managerial judgments (perceptions); and its user friendly nature where users may directly input judgment data without any previous mathematical calculations.…”
Section: Definitions and Preliminaries: Mcdmmentioning
confidence: 99%